2015
DOI: 10.1093/ndt/gfv415
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction models for acute kidney injury following major noncardiac surgery: systematic review

Abstract: Risk prediction models for AKI after major noncardiac surgery are available; however, these models lack validation, studies of clinical implementation and impact analyses. Further research is needed to develop, validate and study the clinical impact of such models before broad clinical uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 26 publications
0
49
1
4
Order By: Relevance
“…In this study, among the patients who survived to hospital discharge after major surgery, 46.8% patients without prior CKD experienced AKI, whereas significantly higher percentage (67.0%) of patients with prior CKD did. In addition, Wilson et al conducted a systematic review of risk prediction models for AKI following major non-cardiac surgery and found that renal insufficiency was an important risk factor of AKI occurrence 25 . In animal models, there is evidence that ischemic AKI is significantly more severe in diabetic mice than in non-diabetic mice 26, 27 .…”
Section: The Aki-ckd Connectionmentioning
confidence: 99%
“…In this study, among the patients who survived to hospital discharge after major surgery, 46.8% patients without prior CKD experienced AKI, whereas significantly higher percentage (67.0%) of patients with prior CKD did. In addition, Wilson et al conducted a systematic review of risk prediction models for AKI following major non-cardiac surgery and found that renal insufficiency was an important risk factor of AKI occurrence 25 . In animal models, there is evidence that ischemic AKI is significantly more severe in diabetic mice than in non-diabetic mice 26, 27 .…”
Section: The Aki-ckd Connectionmentioning
confidence: 99%
“…Prediction models exist for a wide variety of health outcomes, such as cardiovascular disease [5], lung cancer [6], acute kidney injury [7], and infertility treatment success [8]. There is an overwhelming number of models for the prediction of specific outcomes, with, for example, more than 350 prediction models developed for cardiovascular disease in the general population [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several risk stratification systems exist for cardiac surgery patients but the best validated scores predict severe AKI requiring dialysis [14,15] and new studies are needed to validate scores to predict less severe AKI after cardiac surgery [16]. On the other side, non-cardiac surgery has received much less attention and most of the predictive scores predict AKI requiring renal replacement therapy (RRT) following liver transplantation or liver surgery [17]. Kheterpal et al [18] developed a system for non-cardiac surgery for predicting AKI.…”
Section: Clinical Prediction Scoresmentioning
confidence: 99%